The construction of the foreign and the other in Felix Kanitz’s travel notes on Bulgaria - Endreva, Maria (Journal for German and Scandinavian Studies / Списание „Германистика и скандинавистика“, 2021)
The paper examines the functions of representations of foreignness in Felix Kanitz’s travelogues about Bulgaria. It presents the theoretical split in the postcolonial discourse of the traditional opposition of the Own and the Foreign in two new oppositions: the Own - the Other and the Familiar - the Foreign, which have different functions. The first opposition is important for building one’s identity by distinguishing yourself from the other culture, the second is important for understanding the foreign culture and for shortening the distance with it. The examples given concern the subject of materialism of the Bulgarians, who are described as a sympathetic primitive culture.